Paget's Disease Diagnosed on Cranial and Sacroiliac Involvement in Contrast to Normal Alkaline Phosphatase Levels - Gonca Sağlam (Galenos Yayinevi, 2020)
Paget's disease of bone is characterized by a chronic focal bone remodelling disorder, which is usually detected incidentally during routine imagining examinations. Although the measurement of total serum alkaline phosphatase usually provides a general indication of bone turnover in Paget's disease, about 10-15% of patients present with alkaline phosphatase levels within the normal range. The treatment of symptomatic forms relies on bisphosphonates that are efficient in reducing the bone turnover. Here, I present the case of an 80-year-old man suffering from chronic low back pain, and diagnosed as Paget's disease, with normal serum alkaline phosphatase and bone-specific alkaline phosphatase levels.